1990
DOI: 10.1007/bf01967504
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a gold-silver staining method for detection and identification ofCandida species by light microscopy

Abstract: A gold-silver staining procedure was evaluated for detection of Candida species of medical importance. Probes were prepared by coupling lectins or antibodies (polyclonal and monoclonal) directly or indirectly to colloidal gold particles. Structures reacting to these probes were specifically revealed by light microscopy in cells present in infected kidney tissue sections or in isolated yeast cells on glass slides. Definition, contrast and sensitivity were of a high order. Preliminary data showed that it was pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The amount of gold particles observed through the cell wall layers was not enough, however, to permit an accurate description of the toxin secretion modalities. Experimental reproducibility and remarkable labeling of well preserved cellular ultrastructures might be achieved by direct IEM assays, mAb KT4 will be linked to colloidal gold particles and used to detect the toxin secretion in killer yeast cells embedded in Lowicryl resin by IEM or by immunogold-siiver staining on yeast cells dried on glass slides [3]. Preliminary results in indirect IEM have already shown greater fixation of mAb KT4 in the cell wall of Lowicryl embedded killer yeast cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of gold particles observed through the cell wall layers was not enough, however, to permit an accurate description of the toxin secretion modalities. Experimental reproducibility and remarkable labeling of well preserved cellular ultrastructures might be achieved by direct IEM assays, mAb KT4 will be linked to colloidal gold particles and used to detect the toxin secretion in killer yeast cells embedded in Lowicryl resin by IEM or by immunogold-siiver staining on yeast cells dried on glass slides [3]. Preliminary results in indirect IEM have already shown greater fixation of mAb KT4 in the cell wall of Lowicryl embedded killer yeast cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Lectin-fungal cell wall carbohydrate interaction has been demonstrated in several species of medical impor- These studies have shown that most fungi exhibit N-acetyl-D-glucosamine and glucose ⁄ mannose on the cell surface, as inferred by the WGA and Con A binding, respectively. [11][12][13][14][15] Using lectins conjugated with fluorescein isothiocyanate, Robin et al [16] described lectin staining patterns in A. fumigatus and F. solani isolated from cases of eye infections. WGA, UEA-I and Con A intensely stained all the species, whereas PNA did not.…”
Section: Discussionmentioning
confidence: 99%
“…The role of lectins in mycological diagnosis has been reviewed in detail by several authors. 2,3,[11][12][13][14][15][16] Despite the advantages, the development of effective test based on lectin typing will remain difficult until some degree of standardisation of procedures is agreed. Reported specificities of lectins vary depending on the source consulted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…capsuIatum, regardless of serotype. Adsorption of labeled antibodies produced against the most complete H. capsulatum serotype (serotype 1,2,3,4) with cells of Candida albicans yielded a conjugate that stained only //. capsulatum vat capsulatum, I-I.…”
mentioning
confidence: 99%